TANTANGAN PENGEMBANGAN EKOWISATA BAHARI DI PULAU PISANG PESISIR BARAT LAMPUNG - Etik Ipda Riyani; - Tamjuddin (UNIVED Press, 2017)
Etik Ipda Riyani dan Tamjuddin: The purpose of this research is to identify the marine ecotourism development of the Pisang Island that is one of the favourite destination in west coast of Lampung. According to condition and the potencies of this island which likely has a potentiality as a further ecotourism destination and also nature conservation that will bring a revenue for the local communities, local governmemt and also management in west coast of Lampung. There are many problems for managing tourism assets because it requires infrastructure development. The research is located along the coast and marine ecotourism zone of Pisang island. This research is the development as further research of previous research which is about the beach, snorkling and diving zone in north coast of Pisang island by Nugraha and Irfan (2013). The importance of this research is to know the challenges and problems in decision making of tourism-developing sector for local goverment and managemet. The methods of this research are direct survey, observation to collect the data and also interview with respondents. The local communities, tourists, the local entrepreneurs, the local governments such as subdistrict head, district head and head of locat department tourism are the sample of respondents. Data analysis is used by SWOT for formulation. The strategy of development are based on the policies, the marine ecotourism zone, the previous reseach analysis, the experience of local communities, infrastructure demands, human resources and the local culture The involvement of local cummunities, the beach marine ecotourism zone and underwater zone are the result of the research.Key words: Pisang Island, The Challenges Of Policy, Zone, Infrastructure, Human Resources